Do We All Arrive in the Same State of Mind? Understanding Migration to the U.S. from a Psychological Perspective (KULT_online, 2024)
Psychosocial Experiences and Adjustment of Migrants provides an accessible overview of the different types of migration in relation to mental health and adjustment. Using a psychological approach to shed new light on recent migration dynamics, the volume serves as a valuable resource for professionals working in migration-related fields. Consisting of case studies, geographic analysis, and personal narratives, it is a multifaceted work with applicability to various professional fields.